Vectors of a non-profit organization transformation: management, digitalization and financing - A. A. Kolabaeva (Вестник университета)
Economic transformations in the Russian non-profit sector and innovative methods of managing and controlling the financial activities of non-profit organizations (hereinafter referred to as NPOs) have been stidued. The main factors influencing the activities of NPOs, their financing structure, and management model have been analyzed, and potential opportunities and challenges faced by NPOs in the current environment have been identified. NPOs play a significant role in macroeconomic indicators, and their impact on economic, political, and social processes is growing. Particular attention has been paid to NPO funding sources diversification and new digital technologies implementation in the fundraising process. The importance of revising models for accumulating financial resources and creating platforms for interaction with beneficiaries and financial donors has been emphasized. A comprehensive analysis of the factors influencing the functioning of non-profit organizations has been conducted. The transition to a partnership model of interaction with beneficiaries and the transfer of part of social services from the state to NPOs is a dominant factor. Based on the data obtained, a conclusion has been made about forming a new model and structure of NPOs management. The study of the financial sources structure has revealed a change in the financial mechanism with an increase in the share of state funding. Its results are of interest to specialists in the non-profit sector, NPOs representatives, and government officials. The research materials can be used to give recommendations for NPOs development and their financing optimization.